Having the expression for f(x), and knowing the value of f(x) (-22), we just need to equate those expressions:
![f(x)=5x-2=-22](https://img.qammunity.org/2023/formulas/mathematics/college/mtewi3e5nij7w985z27adl1l7oo58pt3lh.png)
Obtaining the following equation with one unknown:
![5x-2=-22](https://img.qammunity.org/2023/formulas/mathematics/college/zbizyrww0kcz0igiko7ahg79ug0den4msd.png)
Solving for x:
![\begin{gathered} 5x=-22+2 \\ \\ 5x=-20 \\ \\ x=-(20)/(5) \\ \\ x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2ykb1ol4usg2ky0u0fdsutgewnnnh7r87w.png)
Answer B: when f(x) = -22, we have that x = -4.
And this will correspond to the point (-4,- 22)